2003
DOI: 10.1155/2003/431686
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endoscopy-Based and Serum-Based Methods for the Diagnosis ofHelicobacter pylori

Abstract: Testing for serological IgG antibodies to H pylori WC was the best to assess whether infection by H pylori was present. Neither the IgA WC nor the IgG CagA ELISAs add significant value in the diagnosis of H pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Enzyme‐linked immunosorbent assay (ELISA) was used to study the presence of IgG antibodies in serum samples by a method validated using local H. pylori strains for the antigen preparation 22 . Data were analyzed using Benchmark Reader (Biorad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme‐linked immunosorbent assay (ELISA) was used to study the presence of IgG antibodies in serum samples by a method validated using local H. pylori strains for the antigen preparation 22 . Data were analyzed using Benchmark Reader (Biorad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of immunoglobulin G (antibodies to an H. pylori whole-cell (WC) antigen preparation or to CagA protein was assessed by enzyme-linked immunosorbent assays (ELISA), as described previously (28,39). In brief, each antigen was dissolved in 0.5 M sodium bicarbonate (pH 9.6) and used to coat microtiter plates overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In a French study, serology and UBT showed positive results significantly more often than culture, histology and the HpSA test in elderly hospitalized patients with severe atrophic corpus gastritis [58]. Also among Mexican adults, invasive diagnostic methods gave positive results less often in patients with atrophic gastritis than in those without atrophic changes [59]. Furthermore, as epidemiological studies are concerned, serology might give the most reliable estimate of the association between H. pylori and the late sequelae of the infection, such as gastric cancer [60].…”
Section: Serological Testsmentioning
confidence: 99%